Influence of climate variability on whitefish (Coregonus lavaretus) year-class strength in a deep, warm monomictic lake - Straile, Dietmar; Eckmann, Reiner; Jüngling, Tobias; Thomas, Gregor; Löffler, Herbert (Oecologia, 2007)
The year-class strength (YCS) of Blaufelchen (Coregonus lavaretus) in deep Upper Lake Constance was analysed for a 52-year period, from 1947 to 1998. Despite strong anthropogenic influences on the species population dynamics due to cultural eutrophication and oligotrophication, intense fishing, and large-scale stocking, the influence of climate variability associated with the North Atlantic Oscillation (NAO) is apparent in the data set. This influence is significant although large-scale stocking of cold-bred larvae was performed to avoid a mismatch of larvae with their food. The importance of stocking on YCS, however, is unclear and was only detectable when analysing a subset of the data. In addition to climate variability a yet unidentified factor related to zooplankton suitability as food for fish larvae, and density-dependent mortality probably related to cannibalism do significantly influence YCS. The NAO seemed to influence YCS twofold, through temperature effects on egg development time and on larval growth rate. The first of these two mechanisms is related to the NAO via a time lag of 1 year due to the specific mixing dynamics of warm monomictic Lake Constance. Hence, a warm winter in the year before spawning results in earlier hatching of larvae, that is, hatching is decoupled from the actual meteorological conditions. This should make the larvae very prone to mismatch the dynamics of their food. However, we found no evidence for such a mismatch in this 52-year data set. published